Parenting pra-orang tua: modal penting mencegah drama keluarga di masa depan - Nisa’, Nabila Iffatun (Maliki Interdisciplinary Journal, 2026)
Pre-parenting is a parenting preparation strategy carried out by parents or even teenagers before officially taking on a new role in the family, which is as a parent. This preparation includes readiness mentally, emotionally, financially, as well as the ability to communicate well and cooperate as a couple. The purpose of this article is to raise awareness among couples who do not yet have children or even teenagers that pre-parenting is very important as a foundational basis to prevent future family drama, which often arises due to a lack of preparation in parenting skills and parents’ unpreparedness in dealing with family dynamics. Generally, conflicts in parenting stem from differences in expectations between parents and children, poor communication patterns, inherited parenting styles from the parents’ own childhood, emotional pressure, and a lack of financial readiness. Through the concept of pre-parenting, they are encouraged to develop an understanding of parenting patterns, recognize old wounds from their own parents’ upbringing, plan the division of roles, manage their lifestyle, and even formulate conflict management strategies early on. Pre-parenting also plays an important role in creating a stable, supportive, and adaptive family foundation, which can minimize stress and family drama after the arrival of a child. With careful preparation, parenting becomes more structured and directed effectively, the relationship between father and mother becomes more harmonious, and the child’s emotional condition can be protected from the negative impact of family conflicts. Therefore, pre-parenting becomes the primary and most effective step in creating a healthy and happy nuclear family.